ANALISIS SEMIOTIKA PERINGATAN KESEHATAN BERGAMBAR PADA KEMASAN ROKOK - Bagus Bramantio; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Visual communication is communication that uses visual language, where visual language is the main force that can be seen and can be used to convey a message that has a defenition, meaning, and a specific purpose, while the visual communication that the author intends is a pictorial health warning on cigarette packs. This study aims to determine how the meaning of denotation, connotation, and the myth of pictorial health warning on cigarette packaging.               This study uses qualitative research methods with Roland Barthes's semiotic analysis which is part of the data analysis method in representative qualitative research. Research subjects in the form of five pictures of health warnings currently in effect on cigarette packaging, as for the objects in this study are the signs (words or symbols) that are on the health warning picture on cigarette packaging media In this study using collection techniques observational data, documentation, and literature study. To achieve the validity of the data in this study the authors used triangulation.               The results of this study indicate the meaning of denotation in the form of the appearance of people suffering from diseases caused by smoking. The meaning of the connotation explains the consequences caused or a form of threat if smoking will cause dangerous diseases such as oral cancer, throat cancer and lung cancer. The myths formed include smoking is a symbol or symbol of virility of a man, this myth is broken by the health warnings illustrated in this edition and there is also a public perception of people who have physical disabilities and people's assumptions at the autopsy of the body. Keywords : Cigarette Packaging, Pictorial Health Warning, Semiotics